Cognitive Fatigue: Multidisciplinary Perspectives on Current Research and Future Applications. 2011
DOI: 10.1037/12343-004
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in sustained attention: Generalizing mechanisms for time awake to time on task.

Abstract: Time on task and time awake are two important influences on human cognitive performance. Both extended periods of wakefulness and extended periods of effort on a single task lead to performance declines (e.g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 46 publications
3
15
0
1
Order By: Relevance
“…It defaults to 50ms, but Stewart, Choo and Eliasmith (2010) have shown that tasks composed of simple productions (such as those implemented to perform the 2AFC and change signal tasks) will have shorter cycle times. This is also consistent with our work with the psychomotor vigilance task (PVT), where we typically find default action time values of approximately 40ms (Gunzelmann, Moore, Gluck, Van Dongen & Dinges, 2010). Rather than refitting the 2AFC task independently, we chose to constrain DAT to the value obtained from the PVT, resulting in the dashed black line in Figure 5.…”
Section: Model Fittingsupporting
confidence: 62%
“…It defaults to 50ms, but Stewart, Choo and Eliasmith (2010) have shown that tasks composed of simple productions (such as those implemented to perform the 2AFC and change signal tasks) will have shorter cycle times. This is also consistent with our work with the psychomotor vigilance task (PVT), where we typically find default action time values of approximately 40ms (Gunzelmann, Moore, Gluck, Van Dongen & Dinges, 2010). Rather than refitting the 2AFC task independently, we chose to constrain DAT to the value obtained from the PVT, resulting in the dashed black line in Figure 5.…”
Section: Model Fittingsupporting
confidence: 62%
“…Finally, the model's alertness levels do not change over the course of the 40-min driving sessions, either upon recognition of a lane violation, or as time on task increases. These dynamics are certainly at play in human driving, and expose important areas for future research, some of which we have begun to explore (Gunzelmann, Moore, Gluck, Van Dongen, & Dinges, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Walsh et al (2017) did not model intrasession changes in PVT performance, in part because PVT sessions tend to be shorter in sleep research (10 min) than what we used (35 min; Veksler & Gunzelmann, 2018). However, we have explored the conjunction of sleep loss and time on task in the PVT in the past (Gunzelmann, Moore, Gluck, Van Dongen, & Dinges, 2011).…”
Section: Different Theories Account For the Impact Of Sleep Loss Versmentioning
confidence: 99%